2021
DOI: 10.5430/ijhe.v10n3p138
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Program Learning Module on Developing Leading Secondary School Teachers in Creative Thinking for Enhancement of Students’ Learning Activities in Thailand

Abstract: The purposes of this study were to: 1) create and develop effective doctoral learning module on leading teachers development program to enhance critical thinking for students in secondary schools under the Office of Basic Education Commission, and 2) evaluate the developed module on its efficiency and effectiveness- its congruence of utility, possibility, and appropriateness, learning achievement of learners, learning retention, and the learners’ satisfaction. Samples were 20 Doctoral degree students in Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
0
0
Order By: Relevance
“…It was investigated by experts and found that the congruence of utility, possibility, and appropriateness in the highest level ( = 4.59, SD = 0.53) before offering the model to the classroom. The efficiency of the module shown the results accordance to the studies of Suda ( 2005); Donbundit (2008); Inruangsri (2011); Krongtanoen (2016); Hasakool, Chianchana, & Stirayakorn (2016); Paphaphasid (2018); Chantarasombat (2020); Chantarasombat, & Meekhamtong (2020); and Chantarasombat & Sombatsakulkit (2021).…”
Section: Discussionsupporting
confidence: 82%
“…It was investigated by experts and found that the congruence of utility, possibility, and appropriateness in the highest level ( = 4.59, SD = 0.53) before offering the model to the classroom. The efficiency of the module shown the results accordance to the studies of Suda ( 2005); Donbundit (2008); Inruangsri (2011); Krongtanoen (2016); Hasakool, Chianchana, & Stirayakorn (2016); Paphaphasid (2018); Chantarasombat (2020); Chantarasombat, & Meekhamtong (2020); and Chantarasombat & Sombatsakulkit (2021).…”
Section: Discussionsupporting
confidence: 82%
“…The development of internet technology has led to the widespread application of BD technology in various fields. Through continuous practical application, BD technology has gradually matured and improved, and many new working methods have been innovated to serve the innovative development of various fields in society (Chantarasombat;Chaiyuth, 2022, p. 35).…”
Section: Significance Of Innovative Hem Workmentioning
confidence: 99%
“…While promoting multicultural education, teachers should use creative thinking development modules to improve the efficiency of educational management (Chantarasombat;Chaiyuth, 2022, p. 35). In the case of work in the field of educational managemen,t in Turkey, it was found that enhancing educational management capacity can contribute to disciplinary cohesion (Gokturk, 2023, p. 184).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we will examine the effectiveness of the media or teaching materials, which is defined as the expectation that students will change their behavior in a satisfactory manner, according to the criteria set by the teacher. The effectiveness will be determined through the "E 1 /E 2 " ratio [19,20], which represents the proportion of the effectiveness of the process to the effectiveness of the outcome [21]. A single teacher will conduct the effectiveness test, evaluating the media or teaching materials with the entire class.…”
Section: Determining the Effectiveness Of Mediamentioning
confidence: 99%
“…3 rd Step: Create a test with three sections. 4 th Step: Have the test reviewed by 5 experts to check for content validity (congruence between the objectives and the items) using the Index of Item Objective Congruence (IOC) [21].…”
Section: E the Process Of Creating An Ar-book Application Using The U...mentioning
confidence: 99%